A journey of a thousand miles : peacekeepers [videorecording (DVD)] - Parveen, Farida (G2P2 Films, 2022)
An all-female Bangladeshi police unit embarks on a risky year-long UN peacekeeping mission into earthquake-ravaged Haiti, leaving their families behind. These police officers shatter stereotypes as they rise to the occasion in the name of building peace.